Relationship between occupational physical activity and cardiometabolic health in female office workers - Mendiola, Trisha Maeve B. 1998-
Physical inactivity has become a prevalent worldwide problem as it is associated with an increased risk of non-communicable diseases and eventual mortality. In the Philippines, it was reported that physical inactivity was prevalent in the adult working population (aged 20 to 59 years). Occupational physical activity (OPA) is a possible way to meet the recommended weekly physical activity levels. Moreover, public health interventions for the promotion of physical activity and reduction of sedentary behaviors (SB) in adults may be developed in the workplace. This research aims to examine the relationship between OPA levels and cardiometabolic health (CMH) indicators of female office workers and compare the CMH indicators between the desk-based group (D Group) and the field-work group (F Group). Using an observational and correlational research design, the study examined the relationship between OPA and CMH indicators. The participants of this study are 189 female office workers (aged 18 to 45 years old) from a local government unit in Central Luzon, who are currently employed for at least a year. The Occupational Sitting and Physical Activity Questionnaire (OSPAQ) was administered to measure their OPA levels at work. Data on cardiometabolic health indicators were collected via the employees’ Annual Physical Exam (APE) results. Results of the study revealed that female office workers engaged in field work have significantly higher levels of total weekly occupational standing, walking, and heavy labor compared to their desk-based counterparts. Meanwhile, desk-based workers have significantly higher occupational sitting time. No significant differences were found between the D Group and the F Group in terms of CMH indicators. A weakly positive correlation was found between the total number of minutes spent sitting at work and BMI, and between heavy labor at work and both SGPT and SGOT levels. The correlation between sitting time at work and BMI was more pronounced in the D Group, while the F Group was reported to have a moderately positive correlation between heavy labor and both SGPT and SGOT levels. Results of the study suggest that there is insufficient evidence to conclude that type of office work moderates the relationship between OPA and CMH indicators among female office workers. This study concludes that female office workers engaged in field work (F Group) did not obtain significantly better CMH results compared to those with solely desk-based jobs (D Group). Future research should investigate other possible factors that may affect the relationship between OPA and CMH to provide a broader understanding of the determinants of CMH among office workers